2012
DOI: 10.1002/pi.4369
|View full text |Cite
|
Sign up to set email alerts
|

Detection of heavy metal ions using a water‐soluble conjugated polymer based on thiophene and meso‐2,3‐dimercaptosuccinic acid

Abstract: This work reports the synthesis of a new water‐soluble conjugated polymer, which interacts specifically with heavy metal ions such as lead and mercury. In order to produce such a material, the fluorescent properties of polythiophene, which constitutes the polymer backbone, were combined with the chelating capacity of meso‐2,3‐dimercaptosuccinic acid, which forms the side‐chain of the conjugated polymer. Thus, the new polymer acts as chemical complexing agent, the fluorescence of which is quenched in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…[1][2][3][4] Applications include lightemitting diodes (OLEDs), [5][6][7][8][9][10] eld effect transistors (OFETs), [11][12][13][14][15] lasers, [16][17][18][19][20] photodetectors, [21][22][23][24][25] sensors, [26][27][28][29] and organic photovoltaic (OPV) devices. [30][31][32][33][34] Functioning is oen based on processes that occur in the excited state, populated for example by optical absorption or electrical stimulus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Applications include lightemitting diodes (OLEDs), [5][6][7][8][9][10] eld effect transistors (OFETs), [11][12][13][14][15] lasers, [16][17][18][19][20] photodetectors, [21][22][23][24][25] sensors, [26][27][28][29] and organic photovoltaic (OPV) devices. [30][31][32][33][34] Functioning is oen based on processes that occur in the excited state, populated for example by optical absorption or electrical stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…The small polymerization effect is mainly ascribed to the large size of the repeat unit, which has already extended conjugation over ve aromatic rings, so that saturation is reached more quickly when more units are added. The partial electron localization on the BT unit in the LUMO level might also prevent effective coupling of this orbital amongst monomers, and conjugation might be reduced by the (calculated) 26 twist angle between the CB and dTBT planes. Additional blue shi for a PCDTBT derivative with bulky side chains occurred upon increase of the twist angle.…”
mentioning
confidence: 99%
“…In addition, Fenton processes are helpful in the removal of heavy metals. Laurenti et al [79] showed that the lowest amount of total organic carbon removal is 50%, but removal can reach 100% under certain conditions. Karci et al [80] showed that in soil and water contaminated by Zn 2+ and Ni 3+ , total organic carbon was completely removed for all runs tested in the present study after pH adjustments.…”
Section: Substrate Concentrationmentioning
confidence: 99%
“…The detection of heavy metal ions is of significance for analytical, biomedical and environmental chemistry due to their adverse effects on human health and the global environment. [1][2][3][4][5][6][7][8][9][10][11][12] Among heavy metal ions, mercury is considered as one of the most extremely toxic and dangerous metal ions for the environment and human health because of its easy accumulation and difficult biodegradation. [13][14][15] Mercury has been widely used in batteries, paints and electronic equipment, leading to an increase of its release to the environment.…”
Section: Introductionmentioning
confidence: 99%